PENINGKATAN KUALITAS PRODUKSI BUDIDAYA UDANG VANAME MELALUI PENYIAPAN PAKAN DAN DIGITALISASI MONITORING AIR TAMBAK SERTA MANAJEMEN PEMASARAN DI DESA SINDANGLAYA, KABUPATEN SERANG - Sugiyanto, Didik; Aulia, Aisa; Antasti, Erico; Esye, Yendi; Rahaju, Sri Mumpuni Ngesti; Sulandari, Uci; Munandar, Agus (Jurnal Abdi Insani, 2025)
The Vaname Shrimp Cultivation Group of Sindanglaya Village, Cinangka District, Serang Regency - Banten which is currently in the form of a cooperative with the name of the Tunas Harapan Core Producer Cooperative. The urgency of this community-based empowerment activity is the need for an increase in technology, especially in the cultivation of vaname shrimp, the problems that occur in the community based on the results of studies and identification of vaname shrimp farmers are known to be the process of preparing shrimp feed. Where the process of mixing shrimp feed still uses manual methods or using hands so that it is not evenly distributed and takes a long time. The next problem in pond management in the process of checking the quality of water content still uses an uncalibrated pH meter. Problems in other areas related to production management and marketing, shrimp pond managers still use the usual method, not following technological developments. The implementation method follows five stages of community service, namely 1. Socialization, 2. Training, 3. Application of technology, 4. Mentoring and evaluation, 5. Sustainability of the program. The results of the activity showed an increase in technology related to the production process of vaname shrimp cultivation, namely the manufacture of a vaname shrimp feed mixer/mixer machine in Sindanglaya Village and the socialization of the use of vaname shrimp feed mixer/mixer machines for vaname shrimp farming groups in Sindanglaya Village, especially in the Tunas Harapan Core Producer Cooperative. Furthermore, improvements related to marketing management in the Community Empowerment (PKM) program were the implementation of a Workshop on the Development of Production Management and Marketing Management based on information technology and assistance in operating online marketing applications. The conclusion in the production sector was an increase in the number of vaname shrimp harvests and an increase in knowledge related to production and marketing management.